2011
DOI: 10.1108/00012531111187261
|View full text |Cite
|
Sign up to set email alerts
|

Does information technology affect the level of information literacy?

Abstract: Purpose -The paper's aim is to study the role of information technology (IT) in the information literacy (IL) of high school students in Hamedan (Iran) through a comparative investigation into the IL skills of students of ordinary and intelligent high schools. An intelligent school refers to a school in which students make use of information technologies in education and have a lesson on "methods of research" and an ordinary school refers to a school in which students do not have any access to information tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The relationship of IL with lifelong learning has been under discussion since last two decades [39,47] as it overcomes the barriers to the lifelong learning process [29,48]. Some empirical studies reported that IL competencies enhance lifelong learning approaches [16,34,49].…”
Section: Il and Lifelong Learningmentioning
confidence: 99%
“…The relationship of IL with lifelong learning has been under discussion since last two decades [39,47] as it overcomes the barriers to the lifelong learning process [29,48]. Some empirical studies reported that IL competencies enhance lifelong learning approaches [16,34,49].…”
Section: Il and Lifelong Learningmentioning
confidence: 99%